The nonprofit risk book : finding and managing risk in nonprofits and NGOs - Feiler, Jesse (De Gruyter, 2017)
The Nonprofit Risk Book guides you through the process of finding, managing and mitigating risks that sap your nonprofit organization's time, finances, and resources. The book will lead you through a systematic process of evaluating what you know best: your organization and its operations. You will learn how to build a list of risks and evaluate each one for its likelihood and impact. After assigning a priority to each risk based on its severity and determining the resources needed to address it, you will be able to create a risk register. From this, you will be able to plan mitigation actions to address each risk and set dates for mitigation plan review and completion. Learn how to use the tools nonprofit leaders need to manage risk in programs and other operations.